2013
DOI: 10.1002/anie.201206708
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Enzyme Stability and Resistance to an Organic Cosolvent by Modification of Residues in the Access Tunnel

Abstract: Mutations targeting as few as four residues lining the access tunnel extended the half‐life of an enzyme in 40 % dimethyl sulfoxide from minutes to weeks and increased its melting temperature by 19 °C. Protein crystallography and molecular dynamics revealed that the tunnel residue packing is a key determinant of protein stability and the active‐site accessibility for cosolvent molecules (red dots).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 35 publications
4
105
0
Order By: Relevance
“…By contrast, a temperature increase from 20 °C to 50 °C led to a significantly reduced E value (E from 174 to 13 for 2-bromopentane, E from 474 to 197 for ethyl 2-bromopropionate, and E from 225 to 83 for methyl 2-bromobutyrate). In a recent study, the thermostability and resistance to organic co-solvents of DhaA from Rhodococcus rhodochrous NCIMB13064 could be drastically improved, as proven by an increase of melting temperature T M up to 19 °C and an extended half-life in 40% DMSO from minutes to several weeks [88]. Modification of the substrate tunnels proved to be a potent tool for obtaining highly improved dehalogenase variants.…”
Section: Dehalogenasesmentioning
confidence: 99%
“…By contrast, a temperature increase from 20 °C to 50 °C led to a significantly reduced E value (E from 174 to 13 for 2-bromopentane, E from 474 to 197 for ethyl 2-bromopropionate, and E from 225 to 83 for methyl 2-bromobutyrate). In a recent study, the thermostability and resistance to organic co-solvents of DhaA from Rhodococcus rhodochrous NCIMB13064 could be drastically improved, as proven by an increase of melting temperature T M up to 19 °C and an extended half-life in 40% DMSO from minutes to several weeks [88]. Modification of the substrate tunnels proved to be a potent tool for obtaining highly improved dehalogenase variants.…”
Section: Dehalogenasesmentioning
confidence: 99%
“…Overall, more than 24 reports have been published in which (co-)solvent resistance has been improved (≥ 15 reports by directed evolution; ≥ 9 reports by semi-rational design). Till today, improved organic (co-)solvent resistance has been reported for at least four enzyme classes including monooxygenases, hydrolases, oxidoreductases, and transferases (Wong et al 2004;Ogino 2009, 2010;Koudelakova et al 2013;Liu et al 2009Liu et al , 2013Martinez and Arnold 1991). The reported beneficial amino acid substitutions provided the insight that how enzymes can be stabilizes organic (co-)solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have shown that reduction of the structural flexibility of protein molecules can be stabilizing strategy in enzyme engineering. For instance, Koudelakova et al [39] reported that they had enhanced the thermal stability and organic cosolvent resistance of haloalkane dehalogenase DhaA from Rhodococcus rhodochrous NCIMB 13064 by increasing the rigidity of an access tunnel. Our previous work also posited that modifying local flexibility in the vicinity of the active site could efficiently improve the thermal stability of lipase B from Candida antarctica [19].…”
Section: Discussionmentioning
confidence: 99%